2009
DOI: 10.1128/jcm.02499-08
|View full text |Cite
|
Sign up to set email alerts
|

Performance Assessment of the GenoType MTBDR plus Test and DNA Sequencing in Detection of Multidrug-Resistant Mycobacterium tuberculosis

Abstract: To facilitate the management of multidrug-resistant (MDR) tuberculosis, two nucleic acid sequence-based methods, the GenoType MTBDRplus test and DNA sequencing, were assessed for the rapid detection of drug-resistant Mycobacterium tuberculosis for the first time in the Asia-Pacific region. The performances of these two assays in detecting the presence of rifampin (rifampicin) (RIF) and isoniazid (INH) resistanceassociated mutations in the rpoB, katG, inhA regulatory region, inhA, and oxyR-ahpC genes were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
57
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 22 publications
(37 reference statements)
9
57
3
1
Order By: Relevance
“…In our study, both susceptible and resistant, mainly MDR, M. tuberculosis strains were evaluated; unfortunately, only a limited number of strains resistant to second-line drugs were evaluated. We found the performance of the GenoType tests in Colombia to be similar to or even better than those described in studies elsewhere, like in Mexico, Brazil, Peru, Chile, Bolivia, France, Italy, Turkey, Spain, Vietnam, the Russian Federation, Ethiopia, and China (4,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). In general, sensitivity, specificity, positive and negative predictive values, and concordance with phenotypic DST support the utility of these tests for the screening of resistance to first-and second-line antituberculosis drugs in our country.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In our study, both susceptible and resistant, mainly MDR, M. tuberculosis strains were evaluated; unfortunately, only a limited number of strains resistant to second-line drugs were evaluated. We found the performance of the GenoType tests in Colombia to be similar to or even better than those described in studies elsewhere, like in Mexico, Brazil, Peru, Chile, Bolivia, France, Italy, Turkey, Spain, Vietnam, the Russian Federation, Ethiopia, and China (4,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). In general, sensitivity, specificity, positive and negative predictive values, and concordance with phenotypic DST support the utility of these tests for the screening of resistance to first-and second-line antituberculosis drugs in our country.…”
Section: Discussionmentioning
confidence: 70%
“…Some studies in China, Vietnam, and South Africa revealed that the most frequent mutations are D94G (gyrA) (36.5%) and A1401G (rrs) (42.1%) in China, D94G (54%) and A1401G (80%) in Vietnam, and D94G (42.4%) in South Africa; these were the most frequent mutations also detected in Colombian strains (4,21,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Mokrousov et al suggested that analysis of other rpoB hot spot codons in Russian region is insignificant for prediction of RIF resistance (5). Studies using other molecular techniques, such as Genotype MTBDRplus assay, identified 95.4% to 99% of RIF-resistant strains in China and South Africa, respectively (21,22). These regional differences could be explained by variations in relative frequencies of investigated mutations (5).…”
Section: Discussionmentioning
confidence: 99%
“…La detección de MTBc por técni-cas moleculares es de gran utilidad porque ha permitido un diagnóstico más rápido respecto del cultivo y más sensible con respecto a la baciloscopia, desarrollándose en los últimos años, varias pruebas diagnósticas [7][8][9][10][11][12] . Una de estas es el ensayo Xpert ® MTB/RIF, que se realiza en el sistema GeneXpert ® (Cepheid, Sunnyvale, CA).…”
Section: Artículo Originalunclassified